Age and Gender Specific Associations between Hyperuricemia and Hypertension: A Cross-Sectional Study in Karachi: Age and Gender Specific Associations between Hyperuricemia and Hypertension - Bocha, Yameen; Jafri, Aliya; Agha, Faiza; Najam, Uzma; Ahmed, Syed Zaryab; Mohyuddin, Samina; Latif, Noureen (Pakistan Journal of Health Sciences, 2025)
Hyperuricemia is increasingly linked to hypertension and various metabolic disorders. Objectives: To investigate the relationship between hyperuricemia and various anthropometric indices among individuals newly diagnosed with hypertension, with an emphasis on identifying potential age- and gender-specific patterns. Methods: The cross-sectional study enrolled 370 newly diagnosed hypertensive adults (230 male and 140 female), aged 18 years and above, using stratified sampling. Anthropometric data, blood pressure, and serum uric acid levels were recorded. Serum uric acid (SUA) levels above 7 mg/dL in males and above 6 mg/dL in females were used to define hyperuricemia. SPSS version 22.0 was used for statistical analysis. Independent t-tests, Pearson’s correlation, Chi-square tests, and ANOVA were applied to analyze the data, with a significance level of p<0.05. Results: The research found a 27.5% prevalence of hyperuricemia, significantly higher in male (33.9%) than female (17.1%) (p<0.001). Male had significantly elevated systolic BP (p=0.043), waist circumference (p<0.001), and serum uric acid levels (p<0.001). Serum uric acid showed positive correlations with systolic BP (p=0.001), diastolic BP (p=0.007), BMI (p<0.001), waist circumference (p<0.001), and age (p=0.024). Hyperuricemic individuals had significantly higher age, BP, BMI, and waist circumference (all p<0.01). Females with hyperuricemia were older (p=0.04) and more frequently in the >50 age group (p=0.036). Conclusions: It was concluded that male showed a higher prevalence of hyperuricemia, while older age was a significant factor for females. These findings suggest the importance of monitoring serum uric acid as an early marker for cardiovascular and metabolic risks, particularly in populations at risk based on gender and age.